1997
DOI: 10.1002/pen.11778
|View full text |Cite
|
Sign up to set email alerts
|

Rheokinetics of curing of epoxy resins near the glass transition

Abstract: The cure of four epoxy‐amine systems was studied by viscometry, dynamic mechanical analysis, and DSC. The investigation was carried on at temperatures below and above the glass transition temperature (Tg) of completely cured products. Viscosity growth in the initial stage of cure is described by an exponential‐type equation, and on approach to the gel‐point by a power law, but the exponent did not coincide with the universal theoretical scaling‐law value. A universal viscosity master curve can be constructed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Because the storage modulus is sensitive to the mutation of the polymer network, it has been suggested that an increase in storage modulus was a measure of the chemical degree of transformation during curing [19] or crosslinking reactions [9]. The storage modulus (G 0 ) monitored here as a function of reaction time in the oscillatory shear flows with different strain amplitudes at 0.4 Hz is shown in Fig.…”
Section: Rheological Evaluationmentioning
confidence: 98%
“…Because the storage modulus is sensitive to the mutation of the polymer network, it has been suggested that an increase in storage modulus was a measure of the chemical degree of transformation during curing [19] or crosslinking reactions [9]. The storage modulus (G 0 ) monitored here as a function of reaction time in the oscillatory shear flows with different strain amplitudes at 0.4 Hz is shown in Fig.…”
Section: Rheological Evaluationmentioning
confidence: 98%
“…Therefore, both the engineering viscosity model and dual-Arrhenius model could not predict the gel point of the system above the critical temperature. The comparison also shows that the two models could only explain the variety of viscosity below the injection temperature of the RTM process at low curing degree rather than the variety of viscosity of the cross-linked system which could be characterized by the scaling model [12].…”
Section: (B) the Results Indicate That The Linear Relation Of B-t Ismentioning
confidence: 98%
“…Gel time is known to be a useful parameter for monitoring the conversion or rate of reaction [11,12]. Time of the crossover of G 0 and G 00 (or tan d = G 00 /G 0 = 1), which is often used as a measure of the gel time, was measured for all samples in this study.…”
Section: Resultsmentioning
confidence: 99%